Effects of N2 and H2S binary impurities on CO2 geological storage in stratified formation – A sensitivity study. (1st November 2018) - Li, Didi; Zhang, Hongcheng; Li, Yang; Xu, Wenbin; Jiang, Xi
Highlights: Effects of the binary impurities N2 -H2 S on carbon storage in stratified formations were investigated. The plume spread and injection-induced pressure build-up in the geologic reservoirs were predicted. The binary impurities had more significant effects on geological storage after injection completion. Increasing ratio of N2 /H2 S resulted in larger plume spread enhancing the dissolution trapping. Permeability distribution and multiple injection on the geological carbon storage were investigated. Abstract: Impurities are unavoidable during CO2 geological storage, and they would potentially affect the plume spread as well as storage capacity and/or efficiency of CO2 . The current study numerically investigated the effects of binary impurities comprising typical components N2 and H2 S on CO2 geological storage in stratified formations. For a fixed total content of the binary impurities, increasing ratio of N2 /H2 S resulted in larger plume spread which meant a higher dissolution trapping efficiency. Because of the backflow of formation brine during the post-injection period, the residual trapping efficiency decreased while the dissolution trapping efficiency increased. This tendency was reinforced with increasing ratio of N2 /H2 S. Besides, this work examined the effects of the ratio of vertical permeability ( kv ) to horizontal permeability ( kh ) and the addition of an injection point in the stratified formation. It was found that lower kv / kh shrunk the plume spread and intensified the maximum pressure build-up. However, in the case of two injection points, the plume in the vertical direction was elongated and the maximum pressure build-up was lessened. The results should be taken into consideration to determine the types and concentrations of impurities allowed in the injected CO2 stream as well as the site selection and injection design for impure CO2 geological storage in stratified formation.